Agregado de trióxido mineral (MTA) e resposta imune: da imunidade inata à reabsorção óssea periapical - Taia Maria Berto Rezende (2008)
Mineral trioxide aggregate (MTA) is a biocompatible root-end filling material. However MTAs influences on the innate and adaptive immune responses and bone resporption in periapical lesions are still unclear. To investigate the effects of MTA on innate immune response, M1 and M2 macrophages were examined in vitro for their viability, adhesion to glass, phagocytosis, production of reactive oxygen and nitrogen species andarginase activity. To assess the effects of MTA on adaptive immune responses, IgG antibody response to Fusobacterium nucleatum (Fn) was evaluated in vivo and memory T cells (Tm) specific to Fn and Peptostreptococcus anaerobius (Pa) were stimulated in vitro with spleenantigen presenting cells and respective antigen in the presence of MTA. MTAs influences on the RANKL-mediated osteoclastogenesis and on the bone resorption activity by mature osteoclasts were tested using RAW264.7 cells and mouse bone marrow cells. MTA did notaffect the M1 and M2 activities. MTA increased serum IgG antibody levels against Fn (p<0.05), indicating an adjuvant activity of MTA. MTA decreased the proliferation of antigen-specific Tm. MTA suppressed IFN-ã or IL-4 (p<0.05) production by Fn-reactive Th2 or Pa-reactive Th1 Tm, respectively, while productions of TNF-á, RANKL and IL-10 fromthese Tm were not affected by MTA. As to bone resorption, MTA inhibited the osteoclastogenesis and osteoclast activity (p<0.05). Conclusion: MTA affected the immune responses as well as bone resorption events in periapical lesions in a manner that benefits host.